Visual and Auditory Spatial Localization in Younger and Older Adults - Xiong, Ying-Zi; Addleman, Douglas A.; Nguyen, Nam Anh; Nelson, Peggy B.; Legge, Gordon E. (Frontiers in Aging Neuroscience, 2022)
Visual and auditory localization abilities are crucial in real-life tasks such as navigation and social interaction. Aging is frequently accompanied by vision and hearing loss, affecting spatial localization. The purpose of the current study is to elucidate the effect of typical aging on spatial localization and to establish a baseline for older individuals with pathological sensory impairment. Using a verbal report paradigm, we investigated how typical aging affects visual and auditory localization performance, the reliance on vision during sound localization, and sensory integration strategies when localizing audiovisual targets. Fifteen younger adults (N = 15, mean age = 26 years) and thirteen older adults (N = 13, mean age = 68 years) participated in this study, all with age-adjusted normal vision and hearing based on clinical standards. There were significant localization differences between younger and older adults, with the older group missing peripheral visual stimuli at significantly higher rates, localizing central stimuli as more peripheral, and being less precise in localizing sounds from central locations when compared to younger subjects. Both groups localized auditory targets better when the test space was visible compared to auditory localization when blindfolded. The two groups also exhibited similar patterns of audiovisual integration, showing optimal integration in central locations that was consistent with a Maximum-Likelihood Estimation model, but non-optimal integration in peripheral locations. These findings suggest that, despite the age-related changes in auditory and visual localization, the interactions between vision and hearing are largely preserved in older individuals without pathological sensory impairments.